Analisis Ekspor Rotan Olahan Di Indonesia - Brigitta Yanda Pratiwi (e-Journal Perdagangan Industri dan Moneter, 2017)
This study aims to looking the development of the export of processed rattan and factors to affect the export of rattan processed in Indonesia during the period 2003-2013. The research results revealed the growth of the export value of rattan processed in Indonesia during the period 2003-2013 has decreased over the last few years. During the years 2003-2013 the development of the largest value of cocoa exports occurred in 2011 amounting to 42,130 thousand USD. On the second aims turned out to be the effect of variable export volume of processed rattan Indonesia, the export price of processed rattan Indonesia, and the exchange rate against the US dollar in affecting exports of rattan processed in Indonesia during the period 2003-2013 (from test Coefficient of Determination). From the test results satstistik together (F-test) between the dependent variable export value of processed rattan Indonesia and the independent variable is the variable export volume of processed rattan Indonesia, the price of processed rattan Indonesia, and the exchange rate of the rupiah against the US Dollar interconnected or have a significant effect.